2018
DOI: 10.1002/hep.30061
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2 Promotes Hepatic Regulatory T Cell Responses and Protects From Biliary Fibrosis in Murine Sclerosing Cholangitis

Abstract: In the multidrug resistance protein 2 (Mdr2) mouse model, low phospholipid bile instigates biliary epithelial injury, sterile inflammation, and fibrosis, thereby recapitulating disease mechanisms implicated in biliary atresia (BA) and primary sclerosing cholangitis. We hypothesize that T lymphocytes contribute to the biliary injury and fibrosis in murine sclerosing cholangitis (SC) and that they are susceptible to suppression by regulatory T cells (Tregs). In juvenile Mdr2 mice, intrahepatic CD8+ lymphocytes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 45 publications
(92 reference statements)
1
37
0
Order By: Relevance
“…Depletion or restoration of Treg cells may become a viable approach in controlling fibrosis in this case. In contrast, in Mdr2 (Abcb4) deficient mice with sclerosing cholangitis, a low dose of IL-2 treatment diminishes biliary injury and fibrosis by the expansion of intrahepatic Tregs ( 44 ).…”
Section: The Role and Mechanisms Of T Cells In Fibrosis And Fibroticmentioning
confidence: 99%
“…Depletion or restoration of Treg cells may become a viable approach in controlling fibrosis in this case. In contrast, in Mdr2 (Abcb4) deficient mice with sclerosing cholangitis, a low dose of IL-2 treatment diminishes biliary injury and fibrosis by the expansion of intrahepatic Tregs ( 44 ).…”
Section: The Role and Mechanisms Of T Cells In Fibrosis And Fibroticmentioning
confidence: 99%
“…With the in‐depth study of the pathogenesis of liver fibrosis, in recent years, it has been found that the CD39–CD73–adenosine pathway has anti‐inflammatory effects in the short term, but in certain cases, it may also promote liver fibrosis through repetitive signaling in defined circumstances (Ferrari et al, 2016). Indeed, Tregs expressing CD39 inhibited the proliferation of hepatic CD8+ T lymphocytes, and CD39 expressed by macrophages can protect from biliary liver injury and fibrosis, while CD39 knockout macrophages, could aggravate liver fibrosis (Peng et al, 2017; Rothweiler et al, 2019; Taylor et al, 2018). Similarly, CD73 knockdown increased cell migration and collagen I expression (crucial features of the fibrogenic process) in HSC lines, and CD73 expression was reduced in activated HSCs (Andrade et al, 2011, 2008).…”
Section: The Cd39–cd73–adenosine Pathway In Liver Fibrosismentioning
confidence: 99%
“…Hepatic CD8 1 T lymphocytes drive biliary injury and fibrosis in murine sclerosing cholangitis. Their proliferation is controlled by hepatic Tregs through the purinergic pathway, which is responsive to IL-2c, suggesting Treg-directed lowdose IL-2 as a potential therapy for sclerosing cholangitis (53). Finally, in transfusion-related acute lung injury (TRALI), daily i.p.…”
Section: Low-dose Il-2 Therapy In Other Inflammatory Conditionsmentioning
confidence: 99%